SHIFT KERJA KAITANNYA DENGAN TINGKAT KELELAHAN KERJA PADA PERAWAT - Iwan Suryadi; Gesit Wijayanti; Seviana Rinawati (Politeknik Kesehatan Kemenkes Makassar, 2022)
Shift work has an important role in human problems that can spread to sleep disorders, physical disorders, psychology, and social problems in the family. Shift work can also affect human physical and psychological changes such as fatigue. This study was conducted to determine the relationship between work shifts and the level of work fatigue in the inpatient service unit of PKU Muhammadiyah Hospital Surakarta. This research method uses an analytical observational design with a cross sectional approach. The research subjects were nurses in the inpatient service unit of PKU Muhammadiyah Surakarta Hospital with a population of 106 people. The sample is 57 people using purposive sampling. The research instrument used a reaction timer for fatigue to measure fatigue and a questionnaire for work shifts, the data were analyzed by statistical tests using one-way ANOVA to show the level of nurse fatigue based on work shifts. Results: The results showed that there were differences in the level of work fatigue of nurses on work shifts in the inpatient service unit at PKU Muhammadiyah Hospital Surakarta where p (value) oneway ANOVA showed p = 0.031. To analyze different groups of shift workers, the data will be analyzed post hoc using the Games Howell test. The results of the Games Howell test show a p value = 0.102 between the morning shift and the afternoon shift, which means that there is no difference in the level of fatigue in the morning shift and afternoon shift. The morning shift and night shift showed a p value = 0.036 and the afternoon shift and night shift showed a p value = 0.036, which means that there are differences in the level of fatigue. Conclusion: There is a difference in the level of work fatigue of nurses based on work shifts in the inpatient service unit of PKU Muhammadiyah Surakarta Hospital and the level of work fatigue due to hard work on the morning shift.